Solar, Stellar and Galactic Connections between Particle Physics and Astrophysics - Carramiñana, Alberto.; Carramiñana, Alberto.; Guzmán Murillo, Francisco Siddharta.; Guzmán Murillo, Francisco Siddharta.; Matos, Tonatiuh.; Matos, Tonatiuh. (Astrophysics and Space Science Proceedings,, 2007)
This book collects extended and specialized reviews on topics linking astrophysics and particle physics at a level intermediate between a graduate student and a young researcher. The book includes also three reviews on observational techniques used in forefront astrophysics and short articles on research performed in Latin America. The reviews, updated and written by specialized researchers, describe the state of the art in the related research topics. This book is a valuable complement not only for research but also for lecturers in specialized course of high energy astrophysics, cosmic ray astrophysics and particle physics.